Safety of besifloxacin ophthalmic suspension 0.6% in refractive surgery: a retrospective chart review of post-LASIK patients - Nielsen SA (Dove Medical Press, 2013)
Steven A Nielsen,1 Marguerite B McDonald,2 Parag A Majmudar31Nielsen Eye Center, Quincy, MA, USA; 2Ophthalmic Consultants of Long Island, Lynbrook, NY, USA; 3Chicago Cornea Consultants Hoffman Estates, IL, USABackground: To evaluate the safety of besifloxacin ophthalmic suspension 0.6% when used in laser-assisted in situ keratomileusis (LASIK) prophylactic antibiotic regimens.Methods: Retrospective surveillance of LASIK surgery cases where besifloxacin ophthalmic suspension 0.6% or moxifloxacin ophthalmic solution 0.5% were prescribed as prophylactic medications. Surgeons from nine US surgical centers provided retrospective case information on surgical outcomes from consecutive cases and reported any adverse events related to the antibacterial used. The primary endpoint was the incidence of adverse drug reactions.Results: A total of 801 case reports (801 eyes; 534 besifloxacin, 267 moxifloxacin) were obtained. The mean (standard deviation [SD]) age at time of surgery was 36.1 (10.6) years. The mean (SD) duration of antibiotic treatment was 8.6 (2.2) days in the besifloxacin group and 8.0 (2.3) in the moxifloxacin group; daily dosing frequency was higher in the moxifloxacin group preoperatively, on the day of surgery, and postoperatively. There were no reports of adverse drug reactions for the 801 eyes in this surveillance. There were no differences between the besifloxacin and moxifloxacin treatment groups in rates of unexpected corneal findings (2.1% vs 1.5%, P = 0.949). The distribution of final visual acuity for the besifloxacin and moxifloxacin groups were similar (P = 0.793). Most cases had a final visual acuity of 20/20 or better.Conclusion: In this retrospective surveillance study, the prophylactic use of besifloxacin ophthalmic suspension 0.6% and moxifloxacin ophthalmic solution 0.5% in patients undergoing LASIK surgery was not associated with any adverse drug reactions.Keywords: Besivance, refractive surgery, adverse drug reactions LASIK, moxifloxacin ophthalmic solution 0.5%, ocular infection prophylaxis